2014
DOI: 10.4172/2167-0420.1000169
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of the Effect of Localized Injections of Autologous Platelet Rich Plasma (PRP) for the Treatment of Female Sexual Dysfunction

Abstract: Currently, accepted treatments for Female Sexual Dysfunction (FSD) are limited to psychological, behavioral, hormonal and psychopharmacologic interventions. Because of the complex and multifactorial nature of FSD, current therapeutic options may leave a subset of women suffering with sexual dysfunction without clinical improvement. As a simple, safe, and natural alternative therapeutic option for treating female sexual dysfunction, a pilot study was undertaken to test the effect, if any, of vaginal and clitora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 15 publications
2
30
2
1
Order By: Relevance
“…PRP is based on the separation of a small amount of blood taken from the patient into a special tube, after which centrifugation is performed and the obtained "PRP" is returned to the same patient by injection. PRP has been used in many areas such as cosmetic use, wound healing, and urologic and orthopedic applications (1)(2)(3) . In many medical diseases, it is becoming increasingly popular among minimally invasive methods with a wide area of use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PRP is based on the separation of a small amount of blood taken from the patient into a special tube, after which centrifugation is performed and the obtained "PRP" is returned to the same patient by injection. PRP has been used in many areas such as cosmetic use, wound healing, and urologic and orthopedic applications (1)(2)(3) . In many medical diseases, it is becoming increasingly popular among minimally invasive methods with a wide area of use.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-rich plasma (PRP) treatment aims to increase the self-healing ability of the human body by increasing neovascularization and collagen formation through the effect of high concentration autologous growth factors administered to the tissue (1) . The most important advantages are it being autologous and reliable (2,3) . Case series, pilot studies, and case reports related to gynecologic use of PRP are observed in the literature (2,3) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several growth factors and cytokines [5,6] in the platelets that are released to cellular damage starting to work together stimulating process of fibroblast collagen synthesis. This pilot study measures the responses of women with stress incontinence, overactive bladder, varying degrees of sexual dysfunction (libido, orgasm, and dyspareunia) and lack lubrication.…”
Section: Introductionmentioning
confidence: 99%